Advances in computers. - Memon, Atif M. (Advances in Computers, 2019)
Advances in Computers, Volume 113, the latest volume in this innovative series published since 1960, presents detailed coverage of new advancements in computer hardware, software, theory, design and applications. Chapters in this updated release include A Survey on Regression Test-case Prioritization, Symbolic Execution and Recent Applications to Worst-Case Execution, Load Testing and Security Analysis, Model Based Test Cases Reuse and Optimization, Advances in Using Agile and Lean Processes for Software Development, Three Open Problems in the Context of E2E Web Testing and a Vision: NEONATE, Experiences with replicable experiments and replication kits for software engineering research, and Advances in Symbolic Execution. Provides in-depth surveys and tutorials on new computer technology Covers well-known authors and researchers in the field Presents extensive bibliographies with most chapters Includes volumes that are devoted to single themes or subfields of computer science.